Intellectual Property Rights Protection Function in Resolving Copyright Disputes - Rachmad Abduh; Fajaruddin Fajaruddin (International Journal Reglement & Society (IJRS), 2021)
Copyright is the exclusive right of the creator or Copyright Holder to regulate the use of the results of casting certain ideas or information. Basically, copyright is the “right to copy a work”. Copyrights can also enable such holders to restrict unauthorized copying of creations from. In general too, copyright has a certain specified validity period. Based on the problems that often occur in copyright, there are mutual claims of creations that always appear at the Director General of Intellectual Property Rights, Menkum HAM, which ultimately in the Commercial Court, this is due to the absence of mandatory registration of works. Law Number 28 of 2014 explains "that copyright is an intellectual property in the field of art and literature that has a strategic role in supporting national development and promoting public welfare as mandated by the 1945 Constitution of the Republic of Indonesia. This research uses normative legal research with descriptive analytical research. Descriptive research was conducted to see the function of protecting intellectual property rights in resolving copyright disputesEmpirical data found in the field are then compared with legal norms in the form of Law Number 28 of 2014 concerning Copyrights. Government Regulation Number 16 of 2020 concerning the Registration of Works and Related Products. So that in the end it can be formulated the functioning of the Protection of Intellectual Property Rights in Resolving Copyright Disputes